Addressing Gender Imbalance in Marriage and Wife-Initiated Divorce in Aceh: Rethinking the Role of Premarital Counselling - Hanapi, Agustin; Husnul, Muhammad; Wahyuni, Yenny Sri; Muqaddas, Abe Yafi (De Jure: Jurnal Hukum dan Syari'ah, 2025)
The persistently high divorce rate in Aceh, predominantly initiated by wives, reflects enduring gender inequality within marital structures. This article critically examines the effectiveness of premarital counseling as a preventive measure against marital dissolution. Using a juridical-normative-empirical approach, qualitative data were collected through interviews with facilitators, registrars, and officials in several Religious Affairs Offices across Aceh Province. Findings reveal that Premarital counseling is frequently implemented in a manner inconsistent with national guidelines, constrained by insufficient duration, lack of certified facilitators, and poor monitoring mechanisms. More importantly, program content often reproduces patriarchal norms rather than addressing structural gender inequalities that contribute to wife-initiated divorce. The article argues that without integrating a gender perspective and addressing underlying socio-legal factors, Premarital counseling remains ineffective in reducing divorce rates. This study contributes to the literature by linking gender imbalance, family resilience, and legal effectiveness, and recommends curriculum reform, professionalization of facilitators, and systematic evaluation to enhance the program’s preventive capacity